Shah Ismail I: Pelopor Penyebaran Teologi Syi’ah di Iran (Kajian Historis) - Ananda, Rayhan Hafizh; Jambak, Mellinda Raswari; Kholil, Ahmad (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
This research was studied to find out the thoughts of Shah Ismail I in spreading Shi'a in Iran and how the existence of Shi'a theology can survive until today in Iran. In addition, this research also intends to describe the pattern of propagation carried out by Shah Ismail I in spreading Shi'ism during the Safavid empire. The method used in this research is descriptive qualitative with a historiographic approach and based on historical studies. The data sources in this research come from literature studies obtained from various books and journals relevant to research studies in the field of Islamic civilization studies regarding the history of the Safavid empire, especially Shah Ismail I. In the data collection stage, researchers collected literature sources obtained from various books and journals. In the data collection method, researchers collect secondary sources such as books, journals, and academic materials that are historical in nature. After that, researchers traced and compiled the data obtained based on the study of historical literature. After completing the data search and collection stage, the next stage is for researchers to analyze all the data obtained by collaborating all data from secondary sources, then all data is presented and analyzed narratively in the form of points. The results showed that Ismail I during his leadership embraced a theocratic pattern at the beginning of his leadership. Then, he also politicized religion as a way to expand his territory to other regions. Shah Ismail I also applied Shiite theology to the daily life of his people. This shows that the existence of the Shi'a sect in Iran is estimated to have started since the reign of the Safavid dynasty led by Shah Ismail I.